Nitric oxide metabolites, nitrative stress, and paraoxonase activity in hepatopulmonary syndrome. (2nd January 2016) - Ames, Paul R. J.; Guardascione, Marianna; Batuca, Joana R.; Arcaro, Alessia; Gentile, Fabrizio; Amitrano, Lucio
Abstract: Aim. To investigate possible abnormalities of vasoactive compounds, nitrative stress, and antioxidant activity of paraoxonase (PONa) in human hepatopulmonary syndrome (HPS), we determined endothelin-1 (ET), nitric oxide (NOx) metabolites, PONa alongside crude plasma nitrotyrosine (NT) as surrogate marker of nitrative stress. Material and methods. Liver cirrhosis (LC) patients with HPS ( n = 12) were matched by age, sex, and Child–Pugh score to LC patients without HPS ( n = 15) and to healthy controls (CTR) ( n = 15); plasma NO2 − (nitrite) (vascular metabolite), NO3 − (nitrate) (inflammatory metabolite), and PONa were determined by a colorimetric assay, ET, and NT by immunoassays. Results. HPS patients showed higher level of ET ( p = 0.0002), NO2 − ( p = 0.002), NO3 − ( p = 0.0001), NT ( p < 0.0001), and lower PONa ( p = 0.0004) than CTR; post-hoc analysis revealed greater ET ( p < 0.05) and NO3 − ( p < 0.005) in LC patients with HPS than in LC patients without HPS. NT correlated to Child–Pugh score within HPS ( p = 0.04) and LC ( p = 0.02). Conclusion. Our HPS patients are characterized by elevated plasma levels of ET and NOx metabolites and lower PONa. Reduced PONa alongside elevated NO3 − and NT suggests that defective antioxidation may favor nitrative stress and both may be implicated in the pathogenesis of HPS.